Strains for studying Spore killer elements in four Neurospora species - B. C. Turner; David D. Perkins (Fungal Genetics Reports, 1993)
This note gives a comprehensive list of stocks useful for working with Spore killer elements, including reference strains for use as testers, genetically marked derivatives, and strains sensitive and resistant to killing by Sk-1K, Sk-2K, and . Geographical site of origin is indicted for the various killer alleles. Many of the strains are newly deposited in FGSC. Some are listed also under other categories. Updated versions of the list will appear in future FGSC Stock Lists (Part IV, Special Purpose Stocks).